Delayed Diagnosis of Esophageal Actinomycosis: A Case Report - Chesney Skaggs; M.D. (WORLD JOURNAL OF CASE REPORTS AND CLINICAL IMAGES, 2025)
Actinomycosis is an uncommon bacterial infection caused by the Actinomyces species. While these bacteria are part of the normal human flora, infection can occur after injury to the mucosal barrier in the setting of certain risk factors. Actinomycosis may involve multiple sites with a variety of presentations requiring a high index of suspicion for diagnosis. We report the case of a 69-yearold female with stage IV breast cancer presenting with odynophagia and epigastric pain. Esophagogastroduodenoscopy (EGD) was remarkable for Grade D esophagitis and a malignant-appearing esophageal stenosis. Histopathology revealed colonies of Actinomyces spp, initially thought to be an incidental finding. Subsequently, the patient was hospitalized with worsening esophageal symptoms and associated weight loss. CT chest showed mid-esophageal wall thickening with surrounding mediastinal attenuation. Given her clinical picture and prior EGD findings, treatment for esophageal actinomycosis with IV penicillin G was initiated. After one month, the patient was transitioned to oral antibiotics and completed a six-month course for actinomycosis with resolution of symptoms. This case highlights a rare presentation of esophageal actinomycosis and the importance of early recognition and treatment. Keywords: Actinomycosis Esophageal Actinomycosis Odynophagia Dysphagia Esophagitis 1. Li J, Li Y, Zhou Y, Wang C, Wu B, Wan J. Actinomyces and Alimentary Tract Diseases: A Review of Its Biological Functions and Pathology. Biomed Res Int. 2018 Aug 26;2018:3820215. doi: 10.1155/2018/3820215. PMID: 30225251; PMCID: PMC6129341. 2. Wong, VK, Turmezei, TD, Weston, VC Actinomycosis. BMJ. 2011;343:d6099. Published 2011 Oct 11. doi:10.1136/bmj.d6099. 3. Könönen E, Wade WG.2015.Actinomyces and Related Organisms in Human Infections. Clin Microbiol Rev 28:.https://doi.org/10.1128/cmr.00100-14. 1. [1] Li J, Li Y, Zhou Y, Wang C, Wu B, Wan J. Actinomyces and Alimentary Tract Diseases: A Review of Its Biological Functions and Pathology. Biomed Res Int. 2018 Aug 26;2018:3820215. doi: 10.1155/2018/3820215. PMID: 30225251; PMCID: PMC6129341. 4. Saad AA, Ragab Y, Ahmed ES, Emad Y, Alghamdi FA, Taha I, Rasker JJ, Saad AA. Pelvi-abdominal ACTINOMYCOSIS as a complication of long-term use of intrauterine device (IUD). The important role of imaging in diagnosis and follow-up. Radiol Case Rep. 2022 Sep 13;17(11):4286-4290. doi: 10.1016/j.radcr.2022.08.035. PMID: 36124319; PMCID: PMC9482080. 5. Sharma S, Hashmi MF, Valentino III DJ. Actinomycosis. [Updated 2023 Aug 7]. In: StatPearls [Internet]. Treasure Island (FL): StatPearls Publishing; 2025 Jan-. Available from: https://www.ncbi.nlm.nih.gov/books/NBK482151/. 6. Valour F, Sénéchal A, Dupieux C, Karsenty J, Lustig S, Breton P, Gleizal A, Boussel L, Laurent F, Braun E, Chidiac C, Ader F, Ferry T. Actinomycosis: etiology, clinical features, diagnosis, treatment, and management. Infect Drug Resist. 2014 Jul 5;7:183-97. doi: 10.2147/IDR.S39601. PMID: 25045274; PMCID: PMC4094581. 7. Lo Muzio, L., Favia, G., Lacaita, M., De Lillo, A., Scully, C., Napoli, A.,Maiorano, E. (2014). The contribution of histopathological examination to the diagnosis of cervicofacial actinomycosis: A retrospective analysis of 68 cases. European Journal of Clinical Microbiology and Infectious Diseases, 33(11), 1915-8. doi:https://doi.org/10.1007/s10096-014-2165-0. 8. Abdalla, Jehad, Myers, James, Moorman, Jonathan. Actinomycotic infection of the oesophagus. Journal of Infection. 2005. Volume 51, Issue 2, E39 - E43. 9. Fukuda, S., Watanabe, N., Domen, T. et al. A case of esophageal actinomycosis with a unique morphology presenting as a refractory ulcer. Clin J Gastroenterol 11, 38– 41 (2018). https://doi.org/10.1007/s12328-017-0797-1. 10. Pillappa R, O'Brien TF, Sullivan JL, Weksler B. Esophageal Actinomycoses Mimicking Malignancy. Ann Thorac Surg. 2016 May;101(5):1967-70. doi: 10.1016/j.athoracsur.2015.07.044. PMID: 27106429.